Selfie Expectancies Among Adolescents: Construction and Validation of an Instrument to Assess Expectancies Toward Selfies Among Boys and Girls - Boursier, Valentina; Manna, Valentina (Frontiers in Psychology, 2018)
Selfie-taking and posting is one of the most popular activities among teenagers, an important part of online self-presentation that is related to identity issues and peer relations. The scholarly literature emphasizes different yet conflicting motivations for selfie-behavior, stressing deeper analysis of psychological factors and the influence of gender and age. Expectancies are “explanatory device[s]” that can help us study adolescent behavior. However, no instruments have been devised that specifically explore the expectations teenagers have about selfies and their influence on selfie-frequency. The current study proposes a short and reliable instrument to identify teen expectancies about selfie-behavior. This instrument was validated using a sample of 646 Italian adolescents (14 to 19 years old) by means of EFA and CFA. We also explore the relationship between selfie expectancies and selfie-frequency, as well as the role of gender in shaping selfies. Our results point towards a 7-factor model that characterizes expectations towards selfies as a multi-dimensional construct linked to both positive and negative perceptions of the nature and consequences of selfies. The overall model fitted the data sufficiently (χ2 = 5067.051 p .0000; CFI = 0.962; TLI = 0.954; RMSEA<=.05: 0.035; SRMR = 0.046), showing an adequate reliability of the scale (α = .830). Bivariate correlations between selfie expectancies and selfie-frequency (r = .338 p< .001) confirmed the convergent validity of the tool. Selfie-sharing is a common practice that is widespread among the participants in this study. Self-promotion represents a positive function of selfies. Selfies promote self-presentation and self-confidence, both in boys and girls. Moreover, selfie expectancies address sexual self-attractiveness, especially among boys. Despite the positive aspects of selfies, our results stress adolescent awareness of the negative consequences of this type of web-exposure. This is especially true among girls whose selfie-behavior is, paradoxically, more frequent than boys. Self-management through selfie-posting is a positive outcome of selfie-behavior that plays a key role among adolescents, even though the dangers of manipulating selfies in order to garner approval from one’s peers need to be considered. The positive psychometric properties of the measure points towards the need for further research on both generalized and specific selfie-behaviors.